Underrepresented drivers of and variability in volatile organic compound emissions from plants - Riches, Mj, author; Farmer, Delphine, advisor; Borch, Thomas, committee member; Davis, Seth, committee member; Szamel, Grzegorz, committee member (Colorado State University. Libraries, 2022)
Volatile organic compounds released from plants interact with the atmosphere in complex ways, e.g., by contributing to the formation and removal of atmospheric oxidants and the production of secondary organic aerosol. These organic compounds include terpenes (polymers of C5H8), organic acids (e.g., formic and acetic), aldehydes (e.g., glycoaldehyde and 2-hexenal), and many other classes of compounds. These compounds are diverse in structure, preventing many assumptions as the physiochemical properties of each species is diverse. Even among the same class of compounds (e.g., C10H16 monoterpene isomers), the atmospheric implications of their emission and reactivity potential can range greatly, as some species contribute more towards the removal of ozone while others are more relevant to secondary organic aerosol formation. Given the diversity of these effects, the quantification and identification of these plant-emitted compounds is a key step to improve predictive models of their emissions and subsequent atmospheric impacts. Measuring the emission of these volatile organic compounds is compounded by their low concentrations, high reactivity, and chemical diversity, and, as of today, there is no single instrument capable of fully investigating the suite of plant-derived emissions. To address this knowledge gap, we used a commercial portable photosynthesis system in combination with numerous analytical instruments, namely chemical ionization mass spectrometry, proton transfer reaction mass spectrometry, and thermal desorption gas chromatography mass spectrometry. We present the modularity of this coupled technique and identify its limitations and the considerations which must be made when performing measurements in the field. We can investigate a greater suite of compounds by coupling the portable photosynthesis system with multiple trace gas instruments simultaneously. The system controls environmental conditions over a broad range applicable to plant physiology and we highlight how background interferences can be mitigated with pre- and post-leaf characterization. This technique provides photosynthetic parameters and direct measurements of leaf-level emissions to improve our understanding of the forces driving these emissions. In addition to developing new analytical techniques, this dissertation identifies numerous environmental factors impacting volatile organic compound emissions that have been so far overlooked or incorrectly represented and expands upon their atmospheric implications. Specifically, we find that the first seasonal snow events cause an initial burst of emissions from a deciduous tree and further changes the identity of speciated compounds compared pre-snow conditions. In this case, excluding speciation of these compounds leads to an underestimation of the atmospheric burden on reactivity and secondary organic aerosol formation. We further identify humidity, which does not exist as a direct emission forcer in most models, as a necessary consideration. Humidity can either have a discrete or synergistic effect with temperature, again complicating integration into models, but inclusion is necessary to address changes in absolute emission rates and the temperature dependence of these emissions. As an overarching theme, this dissertation further presents compelling evidence for considering multiple scales of variability in leaf-level measurements; these measurements are often time consuming, but failure to account for such variability can grossly bias results.
Keywords: leaf-level; plant stress; volatile organic compounds; photosynthesis; biosphere atmosphere exchange; variability